2022
DOI: 10.3389/fpsyg.2022.940882
|View full text |Cite
|
Sign up to set email alerts
|

Spatial stimuli in films: Uncovering the relationship between cognitive emotion and perceived environmental quality

Abstract: ObjectivesThe research paper establishes the impact of spatial stimulus on human cognition and emotion by studying environmental events as cues to understand how people perceive spatial qualities. The medium of film to implement visually disruptive events was used in the research to find the relationship between the subjective evaluation of space and emotional responses.MethodNinety participants participated in watching three films showcasing unexpected spatial stimuli, thus impacting their psychological state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“… Numerous studies have demonstrated the relationship between emotions and cognition (e.g., attitude, intention, etc.) [19,20,22,32,33]. These studies emphasized the effect of emotional components (such as emotional states, fear, sadness, etc.)…”
Section: -1-literature Reviewmentioning
confidence: 99%
“… Numerous studies have demonstrated the relationship between emotions and cognition (e.g., attitude, intention, etc.) [19,20,22,32,33]. These studies emphasized the effect of emotional components (such as emotional states, fear, sadness, etc.)…”
Section: -1-literature Reviewmentioning
confidence: 99%
“…According to the fundamentals of environmental psychology, human-environment behavior and correlation are influenced by mental processes ( Radberg and Steffner, 2003 ; Sternberg and Wilson, 2006 ; Gifford, 2007 ; Pakzad and Bozorg, 2014 ). The affective environmental qualities that determine emotion can help people respond to the space in an emotional evaluation process ( Sakhaei et al, 2022a ), which signifies the environmental capability to change human affection ( Russell and Lanius, 1984 ). Cinematic techniques like camera movement can organize the process of metaphorical mapping in which the inferential logic of image schemas will be able to convey conceptual knowledge of screened contents ( Coëgnarts, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Space is defined as the three-dimensional extension of the universe surrounding the human being, with different forms of relationships, distances and intervals between people and objects (Altan, 1993;Gür, 1996;Kuban, 2018). In filmmaking, space is a parameter where the senses and emotions desired to be aroused in the audience can be concretely planned within the film (Tan, 2018;Sakhaei, 2022). The film would make the audience feel as much as possible in the movie cognitively, both with the locations chosen and the shooting angles of the locations.…”
Section: Introductionmentioning
confidence: 99%